ANALISIS PENGARUH CITRA MEREK PRODUK, KUALITAS PRODUK, DAN HARGA DISKON TERHADAP KEPUTUSAN PEMBELIAN PRODUK MINUMAN KOPI PADA PENGGUNA APLIKASI GRAB FOOD DI KOTA MEDAN - Shisillia Octhaviani; Hendra Jonathan Sibarani (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2021)
This research was conducted in Medan City, West Medan District to observe the effect of Brand Image, Product Quality, Price Discounts on Coffee Drink Purchase Decisions for Grab Food application users in Medan City. This research process uses quantitive research. The population in this study itself is the entire community in West Medan District as many as 73,536 people. The sampling technique used in this study was Simple Random Sampling, with a total sample of 100 respondents. Data collection techniques using questionnaires, data analysis technique used are descriptive analysis and multiple linear regression analysis. The data collected was processed using SPSS for windows version 23. The results showed that partially Brand Image and Price Discounts had a Tcount value of 5,341 for the Brand Image variable, and 7,891 for the Price Discounts variabel which greater than the Ttable value of 1,984. This shows that Brand Image and Price Discounts have a positive and significant effect on Purchase Decisions. And simultaneously the variables Brand Image, Product Quality, and Price Discounts have an Fcount value of 70,165 which greater than Ftable of 2,70. This shows that the variables of Brand Image, Product Quality, and Price Discounts have a positive and significant effect on Purchase Decisions.